A history of the world economy : international economic relations since 1850 - Foreman-Peck, James (New York ; London : Harvester Wheatsheaf, 1995)
The text offers a comprehensive account of the evolution of world trading relations, of the migration of capital and people, of slumps and recessions, and of the successes and failures of exchange rate regimes.
Includes bibliographical references and index.
Keywords: Economic history -- 20th century; Economic history -- 1750-1918.; International economic relations -- History